Integrasi Pengetahuan Tacit Knowledge Perajin Dalam Pengembangan Desain Batik Berbasis AI - Komarudin Kudiya; Saftiyaningsih Ken Atik; M. Djalu Djatmiko (Institut Seni Indoensia Surakarta, 2025)
In the era of digital transformation, the integration of technology and cultural heritage has become a strategic issue, particularly in the preservation and development of batik design. This study aims to integrate artisans’ tacit knowledge—intuitive, experiential, and skill-based understanding—into AI-based design systems without compromising cultural and aesthetic values. Using a qualitative approach through ethnographic design thinking, the research involves participatory observation, in-depth interviews, and visual analysis of traditional batik motifs. The process of converting tacit knowledge into explicit form is carried out through narrative labeling and semantic mapping of batik’s visual elements, which are then incorporated into generative AI models. The findings indicate that this integration can produce batik designs that retain local authenticity while remaining visually relevant to contemporary contexts. Moreover, the active participation of artisans in the AI design process enhances both the aesthetic validity and social acceptance of the outcomes. This study asserts that AI should not be seen as a replacement for artisans, but rather as a collaborative tool that strengthens their role as creative subjects within the digital batik industry ecosystem.